Restoring systemic GDF11 levels reverses age-related dysfunction in mouse skeletal muscle - Sinha, Manisha (2014)
Parabiosis experiments indicate that impaired regeneration in aged mice is reversible by exposure to a young circulation, suggesting that young blood contains humoral “rejuvenating” factors that can restore regenerative function. Here, we demonstrate that the circulating protein Growth Differentiation Factor 11 (GDF11) is a rejuvenating factor for skeletal muscle. Supplementation of systemic GDF11 levels, which normally decline with age, by heterochronic parabiosis or systemic delivery of recombinant protein, reversed functional impairments and restored genomic integrity in aged muscle stem cells (satellite cells). Increased GDF11 levels in aged mice also improved muscle structural and functional features and increased strength and endurance exercise capacity. These data indicate that GDF11 systemically regulates muscle aging and may be therapeutically useful for reversing age-related skeletal muscle and stem cell dysfunction.